The role of exosomal molecular cargo in exosome biogenesis and disease diagnosis - Liu, Meijin; Wen, Zhenzhen; Zhang, Tingting; Zhang, Linghan; Liu, Xiaoyan; Wang, Maoyuan (Frontiers in Immunology, 2024)
Exosomes represent a type of extracellular vesicles derived from the endosomal pathway that transport diverse molecular cargoes such as proteins, lipids, and nucleic acids. These cargoes have emerged as crucial elements impacting disease diagnosis, treatment, and prognosis, and are integral to the process of exosome formation. This review delves into the essential molecular cargoes implicated in the phases of exosome production and release. Emphasis is placed on their significance as cancer biomarkers and potential therapeutic targets, accompanied by an exploration of the obstacles and feasible applications linked to these developments.